Analysis of the Role of Sustainable Entrepreneurship Education to Increase Interest in Entrepreneurship in the Digital Era Through Literature Review Analysis - Mufida, Amatulloh; Utomo, Eko Budi; Sukamto, Dinda Dwi Lukita; Benita, Almas Zerlina; Wulandari, Siti Sri; Susanti, Susanti (IKIP PGRI Bojonegoro, 2024)
This research aims to describe the results of research regarding the analysis of the role of sustainable entrepreneurship education in increasing interest in entrepreneurship in the digital era. This research method is a qualitative study with a Systematic Literature Review (SLR). In this research, SLR is important to reduce sampling by providing differences/relationships between one piece of literature and another. The research sample is articles indexed by Scopus, Google Scholar, and Sinta. The keywords used in searches using Google were